Operations at the seas during the Russo-Turkish War (1787–1792) in the light of the accounts of „Gazeta Warszawska” and „Pamiętnik Historyczno-Polityczny” - Karkocha, Małgorzata (Armia kontra natura, 2020)
In the article the Author discuss the course of naval operations and battles during the Russo-Turkish War of 1787–1792 based on the news from „Gazeta Warszawska” and „Pamiętnik Historyczno-Polityczny”. Both magazines followed the course of this armed conflict with vivid interest, printing reports on both land and sea theater of war operations. They wrote about preparations for subsequent campaigns, the condition and size of enemies fleets. Warsaw periodicals published also information about the numerical strength of the armies, and above all described the most important battles and even minor skirmishes. Therefore, the reader of the Warsaw press obtained quite complete and, what is more important, reliable information about actions taking place at seas, so he could easily form an opinion of this events based on that.